2021
DOI: 10.1002/mde.3458
|View full text |Cite
|
Sign up to set email alerts
|

New brand introduction and selling mode choice for online retailers with network effect

Abstract: This paper builds a game‐theoretic model to examine online retailers' decisions of whether to introduce a new brand and whether to sell it in reselling or agency selling mode if introduced, given one existing brand supplier ex ante. We find it is not always more profitable for the online retailer to introduce the new brand. Interestingly, when determining to introduce the new brand, the online retailer may prefer the agency selling mode even though the commission fee becomes negligible and may not choose the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Chen, Zhuo, and Li (2022) analyze the introduction of the online channel when it comes to different retail solutions by using bilateral bargaining. Zhong and Shen (2022) investigate the introduction of new brands and the choice of selling models for online retailers in the context of a network effect. They find that online retailers prefer the agency selling model when they decide to introduce a new brand, even though the commission may become very small or even negligible.…”
Section: Platform Business Modelmentioning
confidence: 99%
“…Chen, Zhuo, and Li (2022) analyze the introduction of the online channel when it comes to different retail solutions by using bilateral bargaining. Zhong and Shen (2022) investigate the introduction of new brands and the choice of selling models for online retailers in the context of a network effect. They find that online retailers prefer the agency selling model when they decide to introduce a new brand, even though the commission may become very small or even negligible.…”
Section: Platform Business Modelmentioning
confidence: 99%
“…Tian et al (2018) examined the upstream competition between suppliers and found that the online retailer prefers the reselling format when the competition becomes severe. Zhong and Shen (2022) explored the retailer's selling format choice for the introduction of a new brand in the presence of brand competition. The present paper also proceeds from the retailer's perspective to investigate the selling format choice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, this paper is also closely related to the literature on online sales mode choice under competition. Existing literature focuses on supplier competition (e.g., Hagiu & Wright, 2015; Zennyo, 2020; Zhong & Shen, 2021), platform competition (e.g., Abhishek et al, 2016; Liu, Guo, et al, 2021), product competition (e.g., Li et al, 2021; Zhang & Hou, 2022) and channel competition (e.g., Chen et al, 2022; Ha et al, 2021; Yu et al, 2020). For instance, Chen et al (2022) study the sales mode choice of a manufacturer that sells products through the direct channel and the e‐commerce platform.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They reveal that it is beneficial for the manufacturer to adopt agency selling on the platform. Considering that the online retailer may introduce a competing supplier through the agency or reselling mode, Zhong and Shen (2021) explore the retailer's introduction strategy and selling mode choice. By incorporating a manufacturer selling products through the direct or indirect channel, Yu et al (2020) analyze the influence of consumers' channel preferences on the manufacturer's sales mode choice of indirect channel.…”
Section: Literature Reviewmentioning
confidence: 99%